Fine-Tuning MAC-Level Protocols for Optimized Real-Time QoS - Grenier, M.; Navet, N. (IEEE transactions on industrial informatics, 2008)
In distributed real-time systems, meeting the real-time constraints is mandatory, but the satisfaction of other application-dependent criteria is most generally required as well. In particular, networked control systems (NCS) are known to be sensitive to communication delays such as frame response time jitters. Well-known medium access control (MAC) algorithms such as non-preemptive deadline monotonic (NP-DM) or non-preemptive earliest deadline first (NP-EDF) are efficient in terms of bandwidth usage, but they may perform poorly regarding other application-dependent performance criteria. This paper highlights a class of online scheduling policies targeted at scheduling frames at the MAC level, and it provides a schedulability analysis that is valid for all policies within the considered class. As it will be shown, these algorithms are implementable on COTS components (e.g., Controller Area Network controllers) and offer good trade-offs between feasibility and the satisfaction of other application-dependent criteria such as the response time jitter.